Geriatría en la Universidad del Valle: plan, barreras y estrategias - Reyes Ortiz, Carlos Alfonso (Revista Estomatología, 1996)
Geriatrics at the University of Valle has a curriculum plan for its development in hea1th professions at undergraduate and graduate levels, it might lead to the creation of geriatrics specialty. However, for this process there are barriers such as denial of both aging and aged patient, and myths about the aged patient and geriatrics. Also, there are strategies such as promotion of positive attitudes and human values toward the aged, study of normal aging and healthy aged, teaching oftheprofessional-aged patient relationship, geriatrics as mandatory issue, interdisciplinary education, and geriatrics research.